METODE PEMAHAMAN HADIS ULAMA KONTEMPORER NON-AHLI HADIS (Studi Komparatif Antara Persepsi Muhammad Al-Ghazali Dan Pendapat Yusuf Al-Qardhawi) - Muhammad Idris; Taufiqqurrahaman Nur Siagian (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Hadith is the second main source of Islamic teaching after the Qur'an. To understand it in depth, a comprehensive study with certain methods and approaches is needed to be able to capture the intent of a hadith. In accordance with the times, contemporary scholars try to understand a hadith with their respective methods of understanding. Among the contemporary scholars were Muhammad al-Ghazali and Yusuf al-Qardhawi. They offer several methods for understanding the Prophet's hadith. According to al-Ghazali, the method of understanding the Prophet's hadith must be measured from the four criteria of the hadith validity, namely: the hadith must be in accordance with the Koran, the hadith must be in accordance with other saheeh traditions, the hadith must be in accordance with historical facts, the hadith must be in accordance with scientific truth. While Yusuf al-Qardhawi is broader than the four things put forward by Muhammad al-Ghazali.